2011
DOI: 10.1002/ajpa.21486
|View full text |Cite
|
Sign up to set email alerts
|

Intrapopulation variation in stature and body proportions: Social status and sex differences in an Italian medieval population (Trino Vercellese, VC)

Abstract: The phenotypic expression of adult body size and shape results from synergistic interactions between hereditary factors and environmental conditions experienced during growth. Variation in body size and shape occurs even in genetically relatively homogeneous groups, due to different occurrence, duration, and timing of growth insults. Understanding the causes and patterns of intrapopulation variation can foster meaningful information on early life conditions in living and past populations. This study assesses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 52 publications
8
83
0
1
Order By: Relevance
“…A), who was about 156 cm tall, was aged between 30 and 39 years when she died (Figure 2a). Her stature is consistent with the average height calculated for medieval female population in Northern Italy (Vercellotti et al, 2011).…”
Section: Resultssupporting
confidence: 84%
“…A), who was about 156 cm tall, was aged between 30 and 39 years when she died (Figure 2a). Her stature is consistent with the average height calculated for medieval female population in Northern Italy (Vercellotti et al, 2011).…”
Section: Resultssupporting
confidence: 84%
“…Previous anthropological and anthropometric studies have reported intrapopulation variations that could be related to differences in social status [26,29,30]. Therefore, this study compared groups of assumed different social status.…”
Section: Discussionmentioning
confidence: 95%
“…In growing individuals this often involves a slowing or cessation of growth until the stressor is overcome or removed (Martorell, 1989). Depending on the timing and duration of the stress response some elements will experience growth disruptions which produce stress markers whilst others will appear unaffected (Vercellotti et al, 2011). Depending on the timing and duration of the stress response some elements will experience growth disruptions which produce stress markers whilst others will appear unaffected (Vercellotti et al, 2011).…”
Section: Measuring Childhood Health In Human Skeletal Remainsmentioning
confidence: 99%